Correspondence: early identification of COVID-19 positive outpatient children, is it useful? - Gianfranco Trapani; Osama Al Jamal (Hygeia Press di Corridori Marinella, 2020)
The differential diagnosis between COVID-19 and the common cold, or allergic cough, or mild respiratory symptoms with or without fever is not easy for Primary Care Pediatricians (PCPs). According to the official Italian report "Rapporto ISS COVID-19 n. 58/2020" of August 21st, 2020, all children with COVID-19 common symptoms and/or a corporal temperature higher than 37.5°C, are considered as suspected cases and have to be tested with a nasopharyngeal swab. We have identified risk factors that could be useful in PCPs' clinical practice to define priorities in addressing children to the proper diagnostic procedure. For the physical and mental health of the children and their families and to allow the PCPs to fulfill their duty, it is important to look for less invasive tools to perform the proper diagnosis. This should also allow children to go to school and to go on with their daily life.